Driving Quality with Test Automation Tools and Techniques - Srikanth Perla (International Journal of Intelligent Systems and Applications in Engineering, 2016)
Test automation tools and techniques have become an essential part of modern software development, enabling organizations to deliver high-quality software faster and more efficiently. By automating repetitive tasks, enhancing test coverage, and reducing human error, test automation plays a critical role in driving software quality. This paper explores various test automation tools and techniques, focusing on their application in improving software quality in agile development environments. The research presents an analysis of the benefits and challenges associated with implementing test automation and evaluates the impact of different tools on software quality. Techniques like unit testing, integration testing, and regression testing are discussed, along with tools such as Selenium, JUnit, and TestNG that support these practices. The paper also highlights the role of continuous integration and continuous deployment (CI/CD) pipelines in automating testing processes and improving the software release cycle. The study includes case studies and performance metrics to demonstrate the effectiveness of test automation in various software development scenarios. Challenges such as the initial investment, complexity of tool integration, and maintaining automated tests are also discussed. The paper concludes with recommendations for organizations looking to leverage test automation tools to enhance software quality, improve testing efficiency, and support faster release cycles.